2012
DOI: 10.1136/jech-2011-200018
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the achievement of successive periodic health examinations and the risk of dying. Appraisal of a prevention scheme

Abstract: The survival analysis evidenced a significant reduction of all-cause mortality, as well as of cancer and cardiovascular-related mortality, in men and women having benefited from several PHEs. On the other hand, the Cox model by class of propensity score allowed to show a reduction in mortality only in men who returned at least once, in particular that of a higher health interest among the regular beneficiaries of PHE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…However, a previous study reported that the relative mortality risk of those who returned at least once for a new check-up compared with never was 0.75 in men [6]. Also, MHR for all-cause mortality among screened compared to non-screened were 0.74 for men and 0.69 for women [7].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, a previous study reported that the relative mortality risk of those who returned at least once for a new check-up compared with never was 0.75 in men [6]. Also, MHR for all-cause mortality among screened compared to non-screened were 0.74 for men and 0.69 for women [7].…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies rarely controlled lifestyle or comorbidities [7]. Previous literature usually compared screened to non-screened people [6,7,13,14,20]. This is the first study to compare mortality disparities among health examination participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…vs 128 ±1 mm Hg, age-adjusted diastolic BP (DBP): 78 ± 1 mm Hg vs 78 ± 1 mm Hg, total cholesterol: 217 ± 1 mg dl − 1 vs 218 ± 2 mg dl − 1 , tobacco consumption: 31.2 vs 23.3%. In a population similarly collected in France, Henny et al 13 presented the data for 50.116 subjects aged 40-59 years, followed-up for 25 years. They observed a clear difference of about 25% less deaths in those who benefited from two examinations by comparison with those who had only one.…”
Section: Population and Methods Subjectsmentioning
confidence: 99%
“…According to the authors, possible explanations for the finding were that participation in health check-ups might be selective and that most of the included studies were from the 1960s and 1970s, when preventive treatments were not as developed as they are now 5. A French study with a large data set from the 1980s showed that high participation in recurrent health examinations predicted lower mortality in a 25-year follow-up in women and men 4. Japanese studies using data from the 1990s indicated that participation in general health examinations was an independent predictor of lower mortality among women and men,2 also when a wide set of health behaviour characteristics were taken into account 3.…”
Section: Introductionmentioning
confidence: 99%